Biochemical Markers of Diabetic Nephropathy: Selection and Future Perspectives - Dhama A; Chahal A (Advancement and New Understanding in Medical Science Vol. 8, 2024)
Diabetic nephropathy (DN) is the primary reason for end-stage renal disease. As diabetes mellitus is an inflammatory disease that affects the hemodynamic and metabolic axis, therefore identifying inflammatory biomarkers early on is crucial to minimizing the disease's associated consequences. The bad prognosis of terminal stages of Diabetic kidney disease (DKD), necessitating kidney transplant or else early mortality, can be postponed with early detection and optimization of currently available diagnostic alternatives. This chapter provides an overview of biochemical biomarkers being widely used as diagnostic and prognostic tools for diabetic nephropathy.